Material Selection, Manufacturing and Performance Test of Ceramic High‐Temperature Heat Pipes Using Liquid Metals as Working Fluids1. Issue 10 (19th July 2014) - Meisel, Peter; Schöne, Sophie; Lippmann, Wolfgang; Raddatz, Mario; Hurtado, Antonio; Gampe, Uwe; Gude, Maik; Hufenbach, Werner
<x xml:space="preserve">Abstract</x> Heat exchange applications at high temperatures of greater than 800 °C under corrosive or abrasive conditions require heat exchangers based on ceramic materials instead of conventionally used metals. Heat exchangers based on heat pipes are exceptionally suitable since temperature gradients and correspondent thermal stresses are inherently low for this design. At high temperatures greater than 800 °C, the structural material SSiC and working fluids sodium or zinc appear to be the most promising options. Encapsulating the working fluid in ceramic heat pipes with a sealing joint ensuring long term stability and high temperature resistance is particularly challenging. A nickel‐based alloy has been identified as solder material for SSiC heat pipes using sodium as working fluid and a glass solder was used in case of zinc filled heat pipes. Manufactured heat pipes were tested in a hot‐gas test rig at temperatures up to 1000 °C.